Implementasi Pembiasaan Nilai Agama, Moral Dan Sosial Melalui Kegiatan Mendongeng Anak Usia Dini - Armiyanti Armiyanti; Mulyadi Mulyadi; Nasaruddin Nasaruddin (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This study aims to analyze in depth the implementation of the habituation of religious, moral, and social values ??through storytelling activities in early childhood at Aisyiyah Busthanul Athfal Nahung Kindergarten, Maros Regency. The decline in children's ethics and morality in the modern era is a fundamental challenge that underlies the importance of using interactive and fun narrative methods in early childhood education institutions. The method used in this study is descriptive qualitative. Data collection was carried out through technical triangulation which included passive participatory observation of children's daily behavior, in-depth interviews with the principal and class teachers of group B, and a study of daily curriculum documentation. Data analysis was carried out in a flowing manner using the Miles and Huberman model consisting of data reduction, data presentation, and drawing conclusions. The results of the study indicate that storytelling activities are a very effective pedagogical instrument for transforming abstract concepts into concrete behavior. Religious values ??were successfully internalized through the introduction of exemplary Islamic stories that encourage the habituation of daily worship. Moral values ??in the form of honesty and discipline were formed through the process of children's self-identification with the conflicts of the characters in the stories. Meanwhile, children's social values ??experience significant development, moving from an egocentric to a sociocentric orientation, marked by increased empathy and group cooperation in the classroom. The success of this method is largely determined by the consistency of story repetition (habituation), the variety of media used, and the educator's expressive competence in conveying the story's wisdom without appearing patronizing.